Selection of Isolates of Entomopathogenic Fungi and the Bioefficacy of Their Liquid Production against Leptocorisa oratorius Nymphs - SITI HERLINDA; SRI INDAH MULYATI; . SUWANDI (Indonesian Society for microbiology, 2008)
Entomopathogenic fungi are fungi pathogenic to insects and are widely used as biocontrol agents for insect pests. The aim of this research was to study the virulence of Beauveria bassiana and Metarhizium sp. isolates and to evaluate the efficacy of liquid production of those fungi against Leptocorisa oratorius (rice bug). Twelve isolates of B. bassiana and five isolates of Metarhizium sp. were used in this research. Selection result of B. bassiana isolates on third-instar rice bug nymphs showed that the isolate KBC caused the highest mortality rate (93%), while the lowest (46%) was caused by the isolate BBY 725. The shortest time needed to produce 50% mortality (Lethal time, LT50) was 3.52 days (isolate KBC). The longest time (10.36 days) was produced by isolate SLSS. The mortality of rice bug nymphs caused by Metarhizium isolates was only 50-62%. The shortest LT50 of Metarhizium (5.75 days) was produced by isolate Mtm, while the longest (7.46 days) was produced by isolate Mpx. Bioefficacy tests on six kinds of liquid formations of entomopathogenic fungi indicated that all were effective, mostly with LT50 d” two days. The mortality rates of rice bug nymphs caused by bioefficacy of fungus liquid production was generally above 85% up to 100%. The liquid media for entomopathogenic fungi performed better compared with solid media (SDA), as indicated by the greater mortality rate and shorter LT50.